Fine and flavor cocoa: Key aroma compounds and their behavior during processing - Wexler-Goering, Lea (2024)
Introduction. The cocoa varieties (Theobroma cacao L.) that are classified in the global market as fine and flavor, represent 6 % and are marketed at a differentiated price. These varieties have unique characteristics determined by their genotype, and their aroma complexity is a fundamental factor that distinguishes them. Objective. To integrate updated information that provides scientific evidence about fine and flavor cocoa, identify the key compounds that confer this denomination, and describe their behavior during the stages of fermentation, drying, and roasting. Development. Fine and flavor cocoa is highly valued in the market for its unique flavor and aromas, and is especially sought after for the production of gourmet and nutraceutical products. This type of cocoa is cultivated by small producers in the Mesoamerican region, who employ family-based, organic, and sustainable production systems. This region, the main producer of fine and flavor cocoa, faces the risks of losing its valuable biodiversity. It is crucial to conserve cocoa´s genetic diversity and understand its physicochemical components, especially the volatiles responsible for its sensory attributes. Conclusion. The primary processing of cacao, particularly the stages of fermentation and drying, significantly influences its aromatic profile. Controlling and standardizing these processes is essential for producers to obtain their cocoa beans with a differentiated quality, thereby enhancing their value in the market due to their unique sensory characteristics. Future studies should focus on developing standardized methods for fermentation and drying, as well as on conserving the genetic diversity of fine and aromatic cocoa.